Neurophysiological Characteristics of Allgrove (Triple A) Syndrome: Case Report and Literature Review. (September 2021) - Weiman, Daniel I.; Gillespie, Meredith K.; Hartley, Taila; Osmond, Matthew; Ito, Yoko; ,; Boycott, Kym M.; Kernohan, Kristin D.; Lines, Matthew; McMillan, Hugh J.
Allgrove or "Triple A" syndrome is characterized by alacrima, achalasia, and adrenocorticotropic hormone-resistant adrenal insufficiency, as well as central and peripheral nervous system involvement. Patients demonstrate heterogeneity with regard to their age of symptom onset, disease severity, and nature of clinical symptoms. Neurophysiological testing has also shown variability ranging from: motor neuron disease with prominent bulbar involvement, motor-predominant neuropathy, or sensorimotor polyneuropathy with axonal or mixed axonal and demyelinating features. We report an 11-year-old boy who presented with neurological symptoms of progressive spasticity and peripheral neuropathy. His neurophysiological testing confirmed a sensorimotor polyneuropathy with axonal and demyelinating features. Exome sequencing identified compound heterozygote variants in the AAAS gene. We summarize the neurophysiological findings in him and 29 other patients with Allgrove syndrome where nerve conduction study findings were available thereby providing a review of the heterogeneity in neurophysiological findings that have been reported in this rare disorder.